The Effectiveness of Direct Method and Counseling Method Blended Learning to Upgrade College Students' Speaking Skill/ لترقية مهارة الكلام لدي طلاب الجامعة Counseling Learning Method فعالية تمازج بين طريقة المباشرة وطريقة - Suja, Aidillah (UIN Raden Mas Said Surakarta, 2021)
This research is to determine the Implementation of a combination between the Direct Method and the Counseling Learning Method to improve speaking skills for students of Islamic University Sultan Syarif Kasim Riau and to determine the factors that influence this combination Method. This study is experimental research is about research method that is used to search for a specific treatment effect against the other in uncontrolled conditions. By using experimental design Pretest – Posttest None Control Group Design. The data collection method is (1) observation and (2) an oral test. The writer used Tests T Analyze to Analyze the data an oral test. The results of the analysis of the data obtained on the Application Direct Method and Counseling Learning Method in Learning Arabic to improve speaking skills for students of Islamic University Sultan Syarif Kasim Riau based on observations obtained 93.75 % means